Functional dizziness: from phobic postural vertigo and chronic subjective dizziness to persistent postural-perceptual dizziness. Issue 1 (February 2017) - Dieterich, Marianne; Staab, Jeffrey P.
Abstract : Purpose of review: Functional dizziness is the new term for somatoform or psychogenic dizziness. The aim of this study is to review arguments for the new nomenclature, clinical features, possible pathomechanisms, and comorbidities of functional dizziness. Recent findings: The prevalence of functional dizziness as a primary cause of vestibular symptoms amounts to 10% in neuro-otology centers. Rates of psychiatric comorbidity in patients with structural vestibular syndromes are much higher with nearly 50% and with highest rates in patients with vestibular migraine, vestibular paroxysmia, and Ménière's disease. Pathophysiologic processes seem to include precipitating events that trigger anxiety-related changes in postural strategies with an increased attention to head and body motion and a cocontraction of leg muscles. Personality traits with high levels of neuroticism and low levels of extraversion appear as risk factors for anxiety and depressive disorders and increased morbidity in functional disorders. Summary: Correct and early diagnosis of functional dizziness, as primary cause or secondary disorder after a structural vestibular syndrome, is very important to prevent further chronification and enable adequate treatment. Treatment plans that include patient education, vestibular rehabilitation, cognitive and behavioral therapies, and medications substantially reduce morbidity and offer the potential for sustained remission when applied systematically.